Ascertaining yield and grain protein content stability in wheat genotypes having the Gpc-B1 gene using univariate, multivariate, and correlation analysis - Tanin, Mohammad Jafar; Sharma, Achla; Saini, Dinesh Kumar; Singh, Satinder; Kashyap, Lenika; Srivastava, Puja; Mavi, G. S.; Kaur, Satinder; Kumar, Vijay; Kumar, Vineet; Grover, Gomti; Chhuneja, Parveen; et al. (Frontiers in Genetics, 2022)
The high performance and stability of wheat genotypes for yield, grain protein content (GPC), and other desirable traits are critical for varietal development and food and nutritional security. Likewise, the genotype and environment (G x E) interaction (GEI) should be thoroughly investigated and favorably utilized whenever genotype selection decisions are made. The present study was planned with the following two major objectives: (i) GEI determination for some advanced wheat genotypes; and (ii) selection of the best genotypes with high GPC and yield in various environments. Different univariate [Eberhart and Ruessll’s models; Perkins and Jinks’ models; Wrike's Ecovalence; and Francis and Kannenberg's models], multivariate (AMMI and GGE biplot), and correlation analyses were used to interpret the data from the multi-environmental trail (MET). Consequently, both the univariate and multivariate analyses provided almost similar results regarding the top-performing and stable genotypes. The analysis of variance revealed that variation due to environment, genotype, and GEI was highly significant at the 0.01 and 0.001 levels of significance for all studied traits. The days to flowering, plant height, spikelets per spike, grain per spike, days to maturity, and 1000-grain weight were specifically affected by the environment, whereas yield was mainly affected by the environment and GEI. Genotypes, on the other hand, had a greater impact on the grain protein content (GPC) than environmental conditions. As a result, a multi-environmental investigation was necessary to identify the GEI for wheat genotype selection because the GEI was very significant for all of the evaluated traits. Yield, 1000-grain weight, spikelet per spike, and days to maturity were observed to have positive correlations, implying the feasibility of their simultaneous selection for yield enhancement. However, GPC was observed to have a significant negative correlation with yield. Patiala was found to be the most discriminating environment for both yield and GPC and also the most effective representative environment for GPC, whereas Ludhiana was found to be the most effective representative environment for yield. Eventually, two NILs/genotypes (BWL7511 and BWL7508) were selected as the top across all environments for both yield and GPC, and they are considered valuable breeding assets for future breeding programs.